Loss Biodiversity and Ecosystem Services: need for ecological concepts towards sustainable biodiversity management - Sancayaningsih, Retno Peni; Suharsono, S (2011)
Biodiversity is one out of five aspects reccommended by UNESCO in the strategy of sustainable development that we should pay more attention. This covers not only on genetic and species biodiversities, but also on ecosystem biodiversity. Indonesia is one of 8 centers of biodiversity that located in the tropics. Understanding biotic potential of species biodiversity, (bio)-technological and leader-interpreuneurship skills on a certain species may become success keys for improving our commodities in all aspects of health, agriculture, live-stock etc. But gradually, global climate change, inbalanced development, and mismanagement of natural resources may reduce Indonesian mega-biodiversity in land, as well as in aquatic habitats. These degradations happenned mainly because of neglection of the authority, or inadecuate information and education received by the whole society. Through contextual education on ecological basic concepts related to over-harvesting problem (ecosystem, limiting factor, biotic potential, productivity, carrying capacity and conservation), with case-based (SCL) or problem-based learning (PBL) approaches, may change authority mindset towards sustainable development. This furtherly leads or influences the society to become more respect to their sustainable environments/ecosystems and act better as part of the system. Keywords: biodiversity, sustainable, biotic potential, SCL, PBL